Investigations of the antioxidants, antidiabetics and antiviral potential against SARS-CoV-2 of gold functionalized carboxymethyl cellulose - Timothy O Ajiboye; Kolawole A Olofinsan; Nanabi Manamela; Matsabisa G Motlalepula; Modupe O Ogunrombi; Subhendu Dhibar; Frank Eric T Foka; Hazel T Mufhandu; E Erasmus; H G Visser; M Schutte-Smith (Materials Research Express)
A composite of gold and carboxymethyl cellulose (Au-CMC) was prepared from gold(III) chloride and the sodium salt of carboxymethyl cellulose. The prepared composite was characterized by using x-ray diffraction (XRD), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and Energy-dispersive x-ray spectroscopy (EDX). Then, ferric reducing, nitric oxide scavenging and free radical scavenging activities of the synthesized Au-CMC were carried out. In addition, inhibitory activities of the material against α -amylase, α -glucosidase enzymes and SARS-CoV-2 were studied. It was found that the material displayed good antioxidant activities. Especially, its NO scavenging activities was higher than that of vanillin, gold nanoparticles and carboxymethyl cellulose alone. The α -glucosidase enzyme inhibitory effect of the material was better than that of acarbose. Findings also revealed that both CMC and Au-CMC are highly potent against B1.351 and BQ.1.1 variants of SARS-CoV-2. Finally, cytotoxicity studies showed that the two compounds can be used safely in biomedical applications, such as drug delivery, tissue engineering, or as stabilizers in formulations, without concerns.